Green labels and expectations for land use in rural Latin America - Villalobos Jiménez, Alonso (2025)
Over the past two decades (2000–2010), various green labels have emerged to shape Latin American economies, each carrying its own expectations and ambitions regarding land use in rural areas of a region still considered to be in development. A documentary analysis of 40 national reports from LAC countries, produced between 1998 and 2016, identified these expectations and classified them into broad categories that enable an operational understanding of the labels. Notably, the Green Growth and Low Carbon Development approaches display a greater degree of specificity, concreteness, and alignment with the standardized definitions provided by the organizations that promote them. In contrast, despite having a longer history, the concepts of Economics of Sustainable Development and Green Economy show a lack of concreteness and a more ambiguous connection between the aspirations expressed in the reports and the definitions proposed by their respective promoters.